(3eMGSHI GdJcGdja (B:s (3eONd EOGQj (B/s - (3ghQfLQf, JTGQdRs; (3OGJGQ, SQjcGfJ s; (3ahSJQ, LhQL s ((3GdSYhOjI(B: s (3OGQ GdeQjN ddfTQ(B, s, 1996)
(3JNUjU GdJcdaI hGdJcGdja(B- (3JNUjU JcGdja GdefJLGJ GdeTJQcI hGdefJLGJ GdaQYjI(B- (3fXe JMOjO JcdaI GdeQMdI(B- (3GdJda hGdhMOGJ GdeYGO JTZjdgG hGdYhGOe(B- (3JMOjO JcdaI GdYedjI hJMOjO GdJcdaI GQJLGYjG heQGbHI GdeTQhY(B- (3GYOGO GdehGRfI GdQCSeGdjI hJMdjd GdJcdaI(B- (3EYOGO GdehGRfI GdQCSeGdjI(B- (3bjGS GdeRL hGdZdI hGdEfJGLjI(B- (3EOGQI GdJcdaI hGdLhOI hGdhbJ(B- (3EOGQI GdeNRhf haj GdehYO HGdVHW(B- (3ENJjGQ GdfXe GddGeQcRjI hJMOjO CSYGQ GdJMhjd(B- (3ENJjGQ GdfXQ hbjGS GdCOGA hGdecGaCIs
Keywords: (3GdeMGSHIs; (3eMGSHI GdJcGdjas